2007
DOI: 10.1163/156853807779799009
|View full text |Cite
|
Sign up to set email alerts
|

Helminths infecting the lizard Enyalius bilineatus (Iguanidae; Leiosaurinae) from an Atlantic Rainforest area in Espírito Santo state, southeastern Brazil

Abstract: We studied the helminth assemblage of a population of the iguanian lizard Enyalius bilineatus from an Atlantic forest area in Espírito Santo state, southeastern Brazil. Eighteen of the 27 individuals examined (66.7%) harbored helminths. A total of six helminth species were found, including acanthocephalan cystacanths (Centrorhynchidae), and five species of nematodes: Physaloptera lutzi, P. retusa, Oswaldocruzia benslimanei, Rhabdias sp. and larvae of an indeterminate species of Acuariidae. In the context of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
1
16
1
Order By: Relevance
“…Rhabdias has been reported in the Neotropical region in host species of the genera Anolis (Polychrotidae) (Bundy et al, 1987;Dobson et al, 1992;2004), Enyalius (Leisosauridae) (Vrcibradic et al, 2007) and in Tropidurus (Tropiduridade) in the present study. Rhabdias is a parasite less frequently found in the lungs of lizards (Bursey et al, 2003).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Rhabdias has been reported in the Neotropical region in host species of the genera Anolis (Polychrotidae) (Bundy et al, 1987;Dobson et al, 1992;2004), Enyalius (Leisosauridae) (Vrcibradic et al, 2007) and in Tropidurus (Tropiduridade) in the present study. Rhabdias is a parasite less frequently found in the lungs of lizards (Bursey et al, 2003).…”
Section: Discussionsupporting
confidence: 66%
“…Rhabdias is a parasite less frequently found in the lungs of lizards (Bursey et al, 2003). However, it is important to stress that due to the low numbers of studies on endoparasites of lizards in South America (Vrcibradic, 2007), many groups of lizard from so many distinct environments still need to be more fully investigated. The current knowledge of infections by Rhabdias in lizards in Brazil is based on two studies that reported the presence of parasites in the lizards Norops fuscoauratus (Goldberg et al, 2006) and in Enyalius bilineatus (Vrcibradic et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salvator merianae has been well reported as a host for the nematodes of the family Physalopteridae in Brazil, as follow: P. bainae (Pereira et al, 2014); P. lutzi (Brito et al, 2014b); P. retusa , and P. tupinambae (Pereira et al, 2012). In addition, P. lutzi also infects the stomach of the following lizards: Ameiva ameiva (Linnaeus, 1758) (Ribas et al, 1998); C. abaetensis Dias, Rocha andVrcibradic, 2002 (Dias et al, 2005); (Ribas et al, 1995); Enyalius bilineatus Duméril and Bibron, 1837 (Vrcibradic et al, 2007); Eurolophosaurus nanuzae (Rodrigues, 1981) (Fontes et al, 2003); Tropidurus itambere (Rodrigues, 1987) (Van Sluys et al, 1994; T. torquatus (Wied-Neuwied, 1820) (Vrcibradic et al, 2000); T. oreadicus Rodrigues, 1987Rodrigues, (Ávila et al, 2011. According to Anderson (2000), nematodes of the family Physalopteridae use a wide variety of insects as intermediate hosts.…”
Section: Discussionmentioning
confidence: 99%